Rabies Elimination in Rural Kenya: Need for Improved Availability of Human Vaccines, Awareness and Knowledge on Rabies and Its Management Among Healthcare Workers - Chuchu, Veronicah Mbaire; Kitala, Philip Mwanzia; Bichanga, Philet; Ksee, Daniel; Muturi, Mathew; Mwatondo, Athman; Nasimiyu, Carolyne; Maritim, Marybeth; Mutono, Nyamai; Beyene, Tariku J.; Druelles, Sophie; Hampson, Katie; et al. (Frontiers in Public Health, 2022)
Background In Africa, rabies causes an estimated 24,000 human deaths annually. Mass dog vaccinations coupled with timely post-exposure prophylaxis (PEP) for dog-bite patients are the main interventions to eliminate human rabies deaths. A well-informed healthcare workforce and the availability and accessibility of rabies biologicals at health facilities are critical in reducing rabies deaths. We assessed awareness and knowledge regarding rabies and the management of rabies among healthcare workers, and PEP availability in rural eastern Kenya. Methodology We interviewed 73 healthcare workers from 42 healthcare units in 13 wards in Makueni and Kibwezi West sub-counties, Makueni County, Kenya in November 2018. Data on demographics, years of work experience, knowledge of rabies, management of bite and rabies patients, and availability of rabies biologicals were collected and analyzed. Results Rabies PEP vaccines were available in only 5 (12%) of 42 health facilities. None of the health facilities had rabies immunoglobulins in stock at the time of the study. PEP was primarily administered intramuscularly, with only 11% (n = 8) of the healthcare workers and 17% (7/42) healthcare facilities aware of the dose-sparing intradermal route. Less than a quarter of the healthcare workers were aware of the World Health Organization categorization of bite wounds that guides the use of PEP. Eighteen percent (n = 13) of healthcare workers reported they would administer PEP for category I exposures even though PEP is not recommended for this category of exposure. Only one of six respondents with acute encephalitis consultation considered rabies as a differential diagnosis highlighting the low index of suspicion for rabies. Conclusion The availability and use of PEP for rabies was sub-optimal. We identified two urgent needs to support rabies elimination programmes: improving availability and access to PEP; and targeted training of the healthcare workers to improve awareness on bite wound management, judicious use of PEP including appropriate risk assessment following bites and the use of the dose-sparing intradermal route in facilities seeing multiple bite patients. Global and domestic funding plan that address these gaps in the human health sector is needed for efficient rabies elimination in Africa.